2004
DOI: 10.1001/archinte.164.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the Risk of Restless Legs Syndrome in the General Population

Abstract: Restless legs syndrome is a common disease in the general population, affecting women more often than men. It is associated with reduced quality of life in cross-sectional analysis. Parity is a major factor in explaining the sex difference and may guide further clarification of the etiology of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
420
11
34

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 679 publications
(501 citation statements)
references
References 28 publications
36
420
11
34
Order By: Relevance
“…This is interesting since the previous studies (Chervin et al 2002;Walters et al 2004) suggested an increased risk of having another of these disorders when one of them is present. Our fi ndings showed that RLS was quite frequent in subjects with ADHD (almost 34%) when compared with the prevalence rates obtained from epidemiological studies, which reported the prevalence of RLS as almost 11% (Berger et al 2004;Hogl et al 2005). Although we did not have a control group, consistent with previous studies (Cortese et al 2005), our results suggest that RLS is more common in subjects with ADHD than in normal population.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This is interesting since the previous studies (Chervin et al 2002;Walters et al 2004) suggested an increased risk of having another of these disorders when one of them is present. Our fi ndings showed that RLS was quite frequent in subjects with ADHD (almost 34%) when compared with the prevalence rates obtained from epidemiological studies, which reported the prevalence of RLS as almost 11% (Berger et al 2004;Hogl et al 2005). Although we did not have a control group, consistent with previous studies (Cortese et al 2005), our results suggest that RLS is more common in subjects with ADHD than in normal population.…”
Section: Discussionsupporting
confidence: 55%
“…= 9.3 ± 2.5). All subjects were recruited from the general outpatient clinic of a is a common condition with a prevalence of almost 11% (Berger et al 2004;Hogl et al 2005). There are two types of RLS: idiopathic and symptomatic (secondary).…”
Section: Population and Samplingmentioning
confidence: 99%
“…In the group of patients with RLS, 25% of individuals had quitted smoking, but none reported active smoking. These correlations were not yet substantially proven by the studies evaluated, but it is recommended do not smoke at night because smoking can worse the RLS symptoms 16,17 .…”
Section: Resultsmentioning
confidence: 96%
“…Thus, there is no need for polysomnography except when there is suspicion of co-morbidities. Berger et al have used successfully this method 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation